Legalitas dan Pengakuan Perkawinan Siri dalam Perspektif Hukum Keluarga di Era Digital - Ilhammuddin Aribbillah; Nadi Putra; Zia Ulfuat Hisam Abdillah; asrizal Saiin (Al Fuadiy Jurnal Hukum Keluarga Islam, 2025)
Unregistered marriages, which are religiously valid but lack legal recognition, pose various challenges in family law, particularly regarding the protection of women's and children's rights. This study aims to analyze the legal implications of unregistered marriages in the digital era and the legal mechanisms available for obtaining its legitimacy. Using a normative juridical method and a statutory approach, the findings reveal that the legal uncertainty of unregistered marriages affects the legal status of wives and children, including inheritance rights and birth registration. The digital era further complicates this phenomenon with the rise of online ‘unregistered marriages’ services that operate outside the legal framework. Therefore, stricter regulations, the strengthening of marriage validation mechanisms, and the integration of digital technology in marriage registration are necessary to enhance legal protection for families.